Rasionalitas Ekonomi Politik dalam Ratifikasi Konvensi Internasional Perlindungan Hak Pekerja Migran Tahun 2012 - Achmad Zulfikar (Magister Ilmu Politik Universitas Hasanuddin, 2015)
Abstract : International migration has now become everyday phenomena that attract the attention of many countries in the world, either directly involved as sending countries, transit countries, recipient countries, and the combination of the three or is not directly involved. Indonesia is one of the countries directly involved in international migration issues that need to be addressed tactically and strategically. This study is based on a literature review, and interviews with relevant resource persons, including those directly involved in the ratification process. This research broadly finds that the Indonesian government to ratify the International Convention on the Protection of the Rights of Migrant Workers is above the economic interests and political considerations. From the economic aspect, the Indonesian government sought to show its commitment to maintain foreign investment in Indonesia through the protection of foreign workers (TKA) which is driving investment in order to maintain economic growth in Indonesia. As for the political aspect, Indonesia seeks to improve the bargaining position to the countries of destination placement of Indonesian workers (TKI) that these countries provide maximum protection for Indonesian workers overseas.Keywords: Indonesian Government, Indonesian Workers, Foreign Workers, International Convention, Protection of Migrant Workers rights.